Corruption in a Global Context Restoring Public Trust, Integrity, and Accountability - Powell, Melchior; Wafa, Dina; Mau, Tim A. (BASEES/Routledge Series on Russian and East European Studies, 2020)
This book provides an important survey of the causes and current state of corruption across a range of nations and regions. Delving into the diverse ways in which corruption is being combatted, the book explores and describes efforts to inculcate principles of ethical conduct in citizens, private sector actors and public sector personnel and institutions. Corruption is a global condition that effects every type of government, at every level, and has bewitched scholars of governance from ancient times to the present day. The book brings together chapters on a range of state and regional corruption experiences, framing them in terms of efforts to enhance ethical conduct and achieve integrity in government practices and operations. In addition, the book addresses and analyses the theoretical and practical bases of ethics that form the background and historical precepts of efforts to create integrity in government practices, and finally assesses recent international efforts to address corruption on an international scale. This book will be perfect for researchers and upper level students of public administration, comparative government, international development, criminal justice, and corruption.